2018
DOI: 10.3384/diss.diva-152569
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Fennoscandian agricultural history through genetic analysis of aged crop materials

Abstract: Crop plants have undergone a multitude of genetic changes during and following their domestication. The spread of agriculture brought the crops to new geographic regions exposing them to new environments and selection pressures along the way. This gave rise to many local variants with traits favoured both by agricultural practices and the environment. Agriculture was introduced in Fennoscandia (Norway, Sweden, Finland and Denmark) around 4000 BC. The composition of the archaeobotanical record gives some clues … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 226 publications
(263 reference statements)
0
1
0
Order By: Relevance
“…Pointing is a commonly used referential gesture in humans. It is used across cultures and both practised and understood by infants (53). Studies have shown that dogs readily and reliably use several human referential cues to find hidden food (see 3, for review, eg.…”
mentioning
confidence: 99%
“…Pointing is a commonly used referential gesture in humans. It is used across cultures and both practised and understood by infants (53). Studies have shown that dogs readily and reliably use several human referential cues to find hidden food (see 3, for review, eg.…”
mentioning
confidence: 99%